Open-Loop Dynamic Optimization for Nonlinear Multi-Input Systems: Application to Recombinant Protein Production - Pantano, Maria Nadia (2021)
This paper proposes a novel strategy for dynamic open-loop optimization of multivariable nonlinear systems.The methodology is based on the Fourier seriesand orthonormal polynomialsfor the control vector parameterization in a sequential direct solution approach. The advantages of this technique are that a few number of parameters is required for optimization and a smooth control profile is obtained. The proposed strategy is evaluated in the case study of recombinant protein production, that is a nonlinear system with two control actions, the substrate and inhibitor feed flow rate. The algorithms are tested through simulations and the results are compared with those published in the bibliography.